A Peer Review Intervention for Monitoring and Evaluating sites (PRIME) that improved randomized controlled trial conduct and performance - Lane, J; Wade, J; Down, L; Bonnington, S; Holding, P; Lennon, T; Jones, A; Salter, C; Neal, D; Hamdy, F; Donovan, J (2011)
Objective: Good clinical practice (GCP) guidelines emphasize trial site monitoring, although the implementation is unspecified and evidence for benefit is sparse. We aimed to develop a site monitoring process using peer reviewers to improve staff training, site performance, data collection, and GCP compliance. Study Design and Setting: The Peer Review Intervention for Monitoring and Evaluating sites (PRIME) team observed and gave feedback on trial recruitment and follow-up appointments, held staff meetings, and examined documentation during annual 2-day site visits. The intervention was evaluated in the ProtecT trial, a UK randomized controlled trial of localized prostate cancer treatments (ISRCTN20141297). The ProtecT coordinator and senior nurses conducted three monitoring rounds at eight sites (2004-2007). The process evaluation used PRIME report findings, trial databases, resource use, and a site nurse survey. Results: Adverse findings decreased across all sites from 44 in round 1 to 19 in round 3. Most findings related to protocol adherence or site organizational issues, including improvements in eligibility criteria application and data collection. Staff found site monitoring acceptable and made changes after reviews. Conclusion: The PRIME process used observation by peer reviewers to improve protocol adherence and train site staff, which increased trial performance and consistency. © 2011 Elsevier Inc. All rights reserved.